EVALUATION OF COMPRESSIVE AND TENSILE STRENGTH OF HYDROXYAPATITE NANOPARTICLES FROM SPIRAL BABYLON SHELLS (BABYLONIA SPIRATA) AS ALVEOLAR BONE GRAFT MATERIAL CANDIDATES - NASUTION, AINI HARIYANI; ILYAS, SYAFRUDDIN; PRIMASARI, AMETA; WULANDARI, PITU (International Journal of Applied Pharmaceutics, 2025)
Objective: This research is a pilot study that aims to determine the compressive and tensile strength values of nanoparticles hydroxyapatite (nHAp) from Spiral Babylon shells (Babylonia spirata). Methods: The materials used are nHAp made from Spiral Babylon shells using the sol-gel method. The process of hydroxyapatite casting was carried out by mixing hydroxyapatite powder with a binding agent in a ratio of 70% (nHAp) to 30% (Epoxy resin). The specimens were then tested with the Universal Testing Machine to obtain the values of the compressive and tensile strength. Each test was performed in triplicate (n = 3). Results: The values mean of compressive strength obtained was 45.7±3.86 MPa and tensile strength was 6.69±0.53 MPa. Conclusion: Spiral Babylon shells show potential as a candidate material for alveolar bone grafts.